2022
DOI: 10.1177/00420980221082922
|View full text |Cite
|
Sign up to set email alerts
|

Translating the nation through the sustainable, liveable city: The role of social media intermediaries in immigrant integration in Copenhagen

Abstract: This article explores settled Western migrants whose digital content provides recent, mostly Western migrants in Copenhagen with local know-how and city-related information. This new type of informal integration intermediary functions as an emerging digital component of wider urban integration industries that assist migrants with settlement and social integration. We draw on the sociological theory of translation as a social, productive practice that constructs new meanings through selective interpretations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…thus helping them to better adapt to the cultural environment of the host country [7]. Through interpersonal communication and participation in social activities through social media, they can obtain high-quality communication across regions and cultures, which effectively reduces the pressure of cultural adaptation in the host country and helps them to obtain more entertainment and a sense of belonging to the group [8].On the other hand, some scholars have suggested that the use of social media has a negative impact on the individual's cross-cultural adaptation and that the use of social media for cross-cultural adaptation of migrants will enhance their understanding of the cultural environment of the host country [9]. Cross-cultural adaptation of migrants through social media use will increase their dependence on social media, which in the long run will weaken their interpersonal skills in reality, and will not be conducive to a better adaptation to the new social environment.…”
Section: Rationale and Mechanismsmentioning
confidence: 99%
“…thus helping them to better adapt to the cultural environment of the host country [7]. Through interpersonal communication and participation in social activities through social media, they can obtain high-quality communication across regions and cultures, which effectively reduces the pressure of cultural adaptation in the host country and helps them to obtain more entertainment and a sense of belonging to the group [8].On the other hand, some scholars have suggested that the use of social media has a negative impact on the individual's cross-cultural adaptation and that the use of social media for cross-cultural adaptation of migrants will enhance their understanding of the cultural environment of the host country [9]. Cross-cultural adaptation of migrants through social media use will increase their dependence on social media, which in the long run will weaken their interpersonal skills in reality, and will not be conducive to a better adaptation to the new social environment.…”
Section: Rationale and Mechanismsmentioning
confidence: 99%
“…Finally, Fogelman and Christensen (2022) analyse two migrants’ blogs and Instagram accounts about Copenhagen as an emerging digital component of wider integration industries. The content these informal integration intermediaries produce translates their urban know-how to newcomers, while also showcasing their having become (almost) local.…”
Section: Migration Industries Andcity-making: Key Vantage Pointsmentioning
confidence: 99%